U18 Point Guards Vs Shooting Guards/Small Forwards (Wings): Physiological Profile Differences - Ilias Blantas; Panagiotis Androutsopoulos; Konstantinos Ntouvas; Panagiotis Alexopoulos (Universitas Majalengka, 2023)
The purpose of the study was to examine and potentially identify differences in the physiological profiles of U18 male basketball players between the PGs (organisers) and SGs/SFs (Wings) positions. The sample size consisted of 20 young male basketball players who participated in this study (mean weight 77.7 kg, mean height 1.91.6 cm, mean age 16.6 years). Players were classified according to their positions in PG: (n = 10) and in SG/SF (Wings) (n = 10). The players participated in the Developmental Program of the Hellenic Basketball Federation. To determine and compare the physiological profile of the players that participated in the study, the following physiological characteristics were analyzed between the two examined playing positions: CMJ, SJ, SLJ, Illinois Agility Test, 5 - 10m sprint. The sample was studied separately for the two different positions on the field, PGs and SGs/SFs (wings). In the inductive analysis, possible differences between the different positions of the players were examined. Due to limited sample size (N = 20), tests were performed with the non-parametric Mann-Whitney test for two independent samples. This test compares the average values of the ranks (Ranks) between two groups, where the ranks are the position of each measurement in the ordered set of measurements. The main findings of the study suggest that jumping ability (horizontal and vertical) and agility separate PGs from SGs/SFs (wings) at the U18 age level, with the latter position excelling in jumping tests and PGs in agility. In the measurements of the physiological characteristic of the 5-10m sprint speed, no differences were observed between the positions.